MAQÂSHID AL-SYARÎʻAH AND HUMAN RIGHTS PROBLEMS - Purnomo, Bitoh (Universitas Islam Negeri Raden Fatah Palembang, 2020)
Islam is a religion with a welfare orientation not only for Muslimsbut also for all humanity. Thus, a guide in Islam must certainly aim for goodand benefit, and vice versa. However, several guidelines in Islam haveclashed with various things including clashing with Human Rights, such asthe application of Jizyah in an Islamic government is considered contrary tohuman rights, this is because Jizyah is only required for non-Muslims (kafirDzimi) and not obliged by the Muslim community itself. Based on thebackground, this research aims to know, review, and explain how ShariaMaqashid as a method of Instinbath law such a response to human rightsproblems? This research used normative law research with the descriptiveanalytical specification. The law materials used primary, secondary, andtertiary substances. The collection of law materials in this research pursuedby conducting literature research and document studies. The main approachwas taken by doctrinal. Based on the results of this study it can be concludedthat between the Maqsidan and the realization of human rights (HAM) thereis a close and inseparable relationship. The obligation of Jizyah for nonMuslims (kafir Dzimi) in an Islamic government is precisely a form of justicethat does not contrary toward human rights, this because the obligation ofJizyah is a form of non-Muslim contributions (kafir Dzimi) as the obligationof zakat for Muslim communities towards an Islamic government. It can beconcluded that both Muslims and non-Muslims (kafir Dzimi) should not bediscriminated against in the government. Thus, this affirms that theguidance of Islam and human rights does not contradictory to one another ifcomprehensively studied with the Maqashid sharia approach. Keyword: Maqosid, fitrah, attitude